Kepemimpinan Digital Berbasis Tradisi Pesantren: Transformasi Tata Kelola dan Manajemen Pesantren Modern - Sofwan Manaf; Hasim Abdul Jamil; Mastur Mastur; Towil Akhiruddin; Arizqi Arizqi (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2026)
Islamic boarding schools (pesantren) in Indonesia face increasing pressure to adopt digital technologies while preserving their traditional values. However, no systematic digital leadership model has yet integrated these seemingly opposing poles. This study aims to identify how traditional pesantren values are integrated into a digital leadership framework, analyze the challenges and supporting factors for implementation, and evaluate the impact of such a model on governance quality and organizational sustainability. A qualitative single case study design was employed, with data collected through semi-structured interviews at Pondok Pesantren Darunnajah, Jakarta. The findings reveal that values such as Panca Jiwa (sincerity, simplicity, self-reliance, Islamic brotherhood, and freedom) are systematically integrated into digital systems including cashless payments, E-Reports, virtual accounts, and the Darunnajah Smart System. Major challenges include resistance to change, infrastructure disparities, low digital literacy among senior teachers, and balancing digital efficiency with humanistic values. Supporting factors include committed kiai leadership, systematic cadre development, active alumni networks, economic self-reliance, and standardized procedures. The model significantly enhances transparency, accountability, participation, and organizational sustainability. This study concludes that tradition-based digital leadership is not only possible but proven successful, with digitalization serving as an instrument for preserving—not eroding traditional pesantren identity.